2001
DOI: 10.1073/pnas.98.3.858
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive genetic signatures in the Libyan Jews

Abstract: Unlinked autosomal microsatellites in six Jewish and two nonJewish populations were genotyped, and the relationships among these populations were explored. Based on considerations of clustering, pairwise population differentiation, and genetic distance, we found that the Libyan Jewish group retains genetic signatures distinguishable from those of the other populations, in agreement with some historical records on the relative isolation of this community. Our methods also identified evidence of some similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…This study supports and expands the classification of Jewish populations that has been developed by us and others (14)(15)(16). It defines North African Jews as a distinct branch with significant relatedness to European and Middle Eastern Jews, with both being part of a larger Jewish cluster.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This study supports and expands the classification of Jewish populations that has been developed by us and others (14)(15)(16). It defines North African Jews as a distinct branch with significant relatedness to European and Middle Eastern Jews, with both being part of a larger Jewish cluster.…”
Section: Discussionsupporting
confidence: 63%
“…Earlier studies based on blood group markers and serum proteins differentiated North African Jews from other Jewish groups and from non-Jewish North Africans (8)(9)(10)(11)(12)(13). A more recent study identified a distinctive signature for Libyan Jews (15). Here, this signature was confirmed and shown to be shared by Djerban and Tunisian Jews.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This feature makes the use of these distance measures inappropriate. Therefore, we used the proportion of shared alleles distance that is free of the stepwise assumption, enjoys low variance (14), and is widely used with multilocus microsatellite data (11,12,15). We used the FITCH program in the PHYLIP package (16) with the log-transformed proportion of shared alleles distance as implemented in the computer program MICROSAT (17) to construct phylogenetic trees.…”
Section: Methodsmentioning
confidence: 99%
“…Most previous genetic studies focus on time frames that are either too recent (the origin of Jewish communities in the Middle East and Africa; Hammer et al 2000;Nebel et al 2001;Rosenberg et al 2001) or too ancient (the outof-Africa migration of modern humans; Passarino et al 1998;Quintana-Murci et al 1999) to provide insight about the origin and dispersal of Semitic languages and Semitic-speaking populations.…”
Section: Introductionmentioning
confidence: 99%